Exploring the Role of Laughter in Multiparty Conversation - Vogel, Carl; Campbell, Nick (ILLC, 2013)
We report ongoing work on laughter in task based and social multiparty human conversation, outlining work to date on laughter around topic change, annotation procedures developed and current and future work on laughter in relation to topic change, multi modality, and biosignals .
DialDam: Proceedings of the 17th Workshop on the Semantics and Pragmatics of Dialogue (SEMDIAL2013)
PUBLISHED
Amsterdam
Keywords: Laughter; Digital Engagement; Digital Humanities; Computational linguistics; LINGUISTICS; Psycholinguistics; laughter